2018
DOI: 10.1136/bmjopen-2018-025109
|View full text |Cite
|
Sign up to set email alerts
|

Are anxiety levels associated with the decision to participate in a Swedish colorectal cancer screening programme? A nationwide cross-sectional study

Abstract: ObjectivesColorectal cancer (CRC) screening programmes are commonly challenged by low uptake, limiting their potential to reduce CRC burden. We aimed to investigate anxiety levels related to the decision to participate or not in CRC screening among screening participants and non-participants. Further to explore associations between higher anxiety levels related to the decision and individuals’ characteristics.DesignA nationwide cross-sectional study conducted with individuals included in a national randomised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…In line with previous research, women were more likely to report cancer worry 34,35 . Logistic regression analyses showed that this difference had not confounded the association between histology and cancer‐specific distress.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In line with previous research, women were more likely to report cancer worry 34,35 . Logistic regression analyses showed that this difference had not confounded the association between histology and cancer‐specific distress.…”
Section: Discussionsupporting
confidence: 87%
“…Bearing this in mind, our results can be underestimated as people who declined participation in this study might have experienced more negative psychological consequences. This is endorsed by the study of Wangmar et al, in which individuals participating in a CRC screening trial with inadequate health literacy were more likely to experience higher anxiety levels 35 . In addition, individuals with high ASA‐score as well as individuals with no computer and/or digital identity were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This will assist in directing relevant resources and in determining how information is distributed, and in this way, public knowledge will hopefully increase. Furthermore, whether, and in that case to what extent, health literacy (HL), anxiety, educational level, and other factors play a role in the decision‐making process regarding the SCREESCO programme have been investigated within our research group …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, whether, and in that case to what extent, health literacy (HL), anxiety, educational level, and other factors play a role in the decision-making process regarding the SCREESCO programme have been investigated within our research group. 32,33 Regarding Possible explanations for the inability to separate into distinct groups might be that the range among persons and items do not fully match each other and that there is a need for a broader range of items to be able to target a greater proportion of individuals in a sample and thereby their level of SDM. One solution could therefore be to add more items and/or scale steps to the SCREESCO questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Gender is a further important factor for the colonoscopy experience, as women feel more vulnerable [17] and more anxious and [19] report more discomfort and pain [12] compared to men. Women also report higher levels of anxiety related to their screening decision [20], which may impact the colonoscopy experience. Another difference between men and women is the motivation for using conscious sedation during colonoscopy, where women's motives for conscious sedation are to reduce fears, anxiety, and feelings of vulnerability, whereas men's motive is to reduce pain [17].…”
Section: Introductionmentioning
confidence: 99%